Bread-inspired foaming strategy to fabricate a wine lees-based porous carbon framework for high specific energy supercapacitors. Issue 19 (3rd September 2021) - Peng, Hui; Xu, Yipu; Jiang, Yaping; Wang, Xin; Zhao, Rui; Wang, Faqiang; Li, Lu; Ma, Guofu
Abstract : Inspired by the fermentation process of bread, a novel wine lees-based porous carbon framework (WLCF) having high energy density and excellent long-term stability is prepared via one-step sodium bicarbonate foaming and activation strategy. Abstract : Herein, inspired by the fermentation process of bread, a novel wine lees-based porous carbon framework (WLCF) with a three-dimensional porous structure is prepared via a one-step simple and environmentally friendly sodium bicarbonate foaming and activation strategy. Based on the dual functions of a self-generating expansion gas and activator originating from the thermal decomposition of sodium bicarbonate, the resulting WLCF presents a fluffy carbon frame structure, high specific surface area (1494.6 m 2 g −1 ) and high nitrogen doping effect (7.5 wt%), which significantly improve the electrochemical performance. The symmetrical supercapacitor assembled with WLCF electrodes and Na2 SO4 aqueous electrolyte exhibits a wide and stable voltage window of 2 V and a high energy density of 18 W h kg −1 at the power density of 225 W kg −1 . Furthermore, the supercapacitor fabricated based on WLCF electrodes and ionic liquid ([Emim]BF4 ) electrolyte delivers an ultrahigh output voltage up to 4 V, a high energy density of 54 W h kg −1 at a high power density of 401 W kg −1, and a superior capacitance retention of 90% after 100 000 cycles. The green preparation of a biomass-based porous carbon framework and the successful realization of wide operating voltage provide a promising strategy toward achieving high energy density supercapacitors.